Odpowiedzi

Najlepsza Odpowiedź!
2009-12-27T15:12:23+01:00
Α = 30*
h = 1 m
f = 0,2

l = h / sin α
l = 1 / sin 30* = 2 m

l = (a • t^2) / 2
Po przekształceniu:
t = √[(2 • l) / a]
a = Fw / m
Fw = Fs - T
Fs = sin α • m • g
T = f • Fn
Fn = cos α • m • g
a = g • (sin α - f • cos α)
t = √{(2 • l) / [g • (sin α - f • cos α)]}

t = √{(2 • 2) / [10 • (sin 30* - 0,2 • cos 30*)]}
t = 1,11 s

v = a • t
v = √(2 • l • a)
v = √[2 • l • g • (sin α - f • cos α)]

v = √[2 • 2 • 10 • (sin 30* - 0,2 • cos 30*)]
v = 3,62 m/s
6 4 6